A method for preparing a low-warpage reinforced POM composite material

By cleaning, surface oxidizing and chemical grafting of carbon fibers, and combining them with polycrystalline mullite fibers and glass fibers, the problems of uneven fiber distribution and high cost in the prior art are solved, and the preparation of POM composite materials with high strength, low warpage and thermal stability are achieved.

CN119775709APending Publication Date: 2025-04-08FUZHOU TEPLER NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510085668.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, mineral-enhanced low warping POM materials are difficult to achieve uniform distribution of glass fibers and nanocarbon fibers in polyformaldehyde raw materials, resulting in limited performance improvement, and nanocarbon fibers are expensive and difficult to be widely used.

Method used

Modified carbon fibers that have been cleaned, surface oxidized and chemical grafted are used, combined with polycrystalline mullite fibers and glass fibers, and mixed with POM materials for melt extrusion and granulation, which significantly reduces fiber pull-off and improves shear strength and interface binding force.

Benefits of technology

It achieves the effect of high shear strength, excellent interface bonding force and significantly improves the interlayer shear strength ILSS, while reducing the use of carbon fiber, controlling costs, and promoting low warpage and thermal stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005250072590000111
    Figure BDA0005250072590000111
Patent Text Reader

Abstract

The present application discloses a method for preparing a low-warpage reinforced POM composite material, relates to the technical field of polymer materials, and includes a carbon fiber modification treatment part and a component mixing and granulation part; the carbon fiber modification treatment part includes cleaning, surface oxidation and chemical grafting of carbon fiber; the component mixing and granulation part includes the following steps: step 1, mixing: 80-100 parts of POM, 12-18 parts of polycrystalline mullite fiber, 7-10 parts of glass fiber, and 0.2-0.6 parts of anti-aging aid are put into a mixer and mixed evenly to obtain a mixture; step 2, crushing: the mixture is introduced into a crushing grinder and crushed and ground to obtain a powdered mixture; step 3, drying: the powdered mixture is vacuum dried to obtain a dry mixture; step 4, granulation: the dry mixture and 2-5 parts of modified carbon fiber by weight are respectively introduced into a twin-screw extruder, and melt extrusion granulation is performed. The present application has the effect of realizing cost control, improving thermal stability and low warpage tracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and in particular to a method for preparing a low-warping reinforced POM composite material. Background Art

[0002] POM material is a kind of synthetic resin material, also called polyoxymethylene resin. The polymer obtained by the polymerization of formaldehyde has a low degree of polymerization and is easy to thermally depolymerize, and can be used as a raw material for organic chemical industry and synthetic resin, or as a drug fumigant. Properties White flammable crystalline powder with a formaldehyde odor. POM material dissolves slowly in cold water and dissolves quickly in hot water. The solubility in water at 20°C is 0.24g / 100cm 3 H2O, is insoluble in ethanol and ether, but soluble in caustic soda and potassium solutions. Generally, POM material is a hard and dense material with a smooth and shiny surface, light yellow or white, and the thin wall part is translucent.

[0003] The Chinese patent application document with publication number CN109825028A discloses a mineral-reinforced low-warpage POM material and its preparation process. The mineral-reinforced low-warpage POM material is made of the following raw materials in parts by weight: 90-100 parts of polyoxymethylene, 10-20 parts of glass fiber, 12-16 parts of nano-carbon fiber, 1-5 parts of formaldehyde absorber, 3-7 parts of pearl powder, 0.3-0.8 parts of antioxidant, 2.4-2.8 parts of white oil, 1.5-1.9 parts of formamide, 0.8-1.2 parts of spermaceti, 0.7-1.5 parts of isotriglyceride, and 3-5 parts of lubricant.

[0004] However, in the process of improving the high temperature resistance and strength of the mineral-reinforced low-warping POM material by using glass fiber and nano-carbon fiber to achieve low warping, it is difficult to evenly distribute the glass fiber and nano-carbon fiber in the polyoxymethylene raw material, and based on the principle of improving the performance of the mixture, the amount of added glass fiber and nano-carbon fiber determines the performance improvement prospect of the POM material. However, the price of nano-carbon fiber is high, and it is difficult to widely use the POM material with improved performance. As a result, it is difficult to promote and apply it, and it is impossible to bring about economic benefits through large-scale laying and utilization, which needs to be improved. Summary of the invention

[0005] In view of this, the purpose of this application is to provide a method for preparing a low-warpage reinforced POM composite material to achieve the purpose of controlling costs, improving thermal stability and low warpage. The specific scheme is as follows:

[0006] A method for preparing a low-warpage reinforced POM composite material, comprising a carbon fiber modification treatment part and a component mixing and granulation part;

[0007] The carbon fiber modification treatment part includes cleaning, surface oxidation and chemical grafting of carbon fibers; the component mixing and granulation part includes the following steps:

[0008] Step 1, mixing: 80-100 parts by weight of POM, 12-18 parts of polycrystalline mullite fiber, 7-10 parts of glass fiber, and 0.2-0.6 parts of anti-aging additive are put into a mixer and mixed evenly to obtain a mixture;

[0009] Step 2, crushing: introducing the mixture into a crushing and grinding machine for crushing and grinding to obtain a powder mixture;

[0010] Step 3, drying: vacuum drying the powder mixture to obtain a dry mixture;

[0011] Step 4, granulation: introducing the dry mixed material and 2-5 parts by weight of the modified carbon fiber into a twin-screw extruder respectively, and melt-extruding and granulating;

[0012] Wherein, the chemical grafting is an organosilane grafting treatment using the following molecular formula:

[0013] R2CH2NH(CH2)3Si(OR1)3

[0014] In the formula: R1 is C1-C4 alkyl; R2 is -CN, -NH2, -Cl, -Br or -HSO3.

[0015] Preferably: the carbon fiber is cleaned by rinsing with deionized water at 40-60°C for 20-40s, the surface oxidation of the carbon fiber is carried out by anodic electrolytic oxidation, and the cleaned carbon fiber is used as the anode, the electrolyte is sodium hydroxide, nitric acid, hydrochloric acid or potassium permanganate, and the voltage is controlled to 1.4-1.8V, and the surface oxidized carbon fiber is rinsed with deionized water.

[0016] Preferably, the oxygen content of the surface-oxidized carbon fiber is 0.1%-12%.

[0017] Preferably, the chemical grafting is performed by immersing the surface-oxidized carbon fibers in an organic silane solution with a concentration of 0.1-0.8%, and then taking them out and subjecting them to cold plasma treatment; wherein the solvent is acetone.

[0018] Preferably: the anti-aging aid is a hindered phenol antioxidant.

[0019] Preferably, the particle size of the powder mixture is less than 200 nm.

[0020] Preferably, the mixture further comprises 0-3 parts by weight of a functional additive, wherein the functional additive comprises a formaldehyde adsorbent and / or a lubricant.

[0021] Preferably, the formaldehyde adsorbent is copolyamide COPA, and the lubricant is silicone masterbatch, PE wax or calcium stearate.

[0022] It can be seen from the above scheme that the present application provides a method for preparing a low-warping reinforced POM composite material. The method for preparing a low-warping reinforced POM composite material adopts modified carbon fibers that have been cleaned, surface oxidized and chemically grafted, so that the surface monomer adsorption capacity of the carbon fibers after surface oxidation is improved, and then after the organic silane is used as a monomer and chemically grafted with the carbon fibers, when mixed with POM, polycrystalline mullite fiber and glass fiber as the main components for melt extrusion and granulation, the fiber pull-out phenomenon using the fracture is significantly reduced, and the method has the effects of high shear strength, excellent interface bonding strength and significantly improved interlaminar shear strength ILSS. DETAILED DESCRIPTION

[0023] The following will be clearly and completely described in conjunction with the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0024] It should be mentioned that the POM in the embodiment of the present application is 500P purchased from DuPont; the hindered phenol antioxidant is 2,4-dimethyl-6-phenylenediol purchased from Wuhan Kanos Technology Co., Ltd., of course, other hindered phenol antioxidants can also be used, which will not be elaborated here; mullite polycrystalline fiber is purchased from Forsman; glass fiber is purchased from Nantong Runfeng Petrochemical Co., Ltd.

[0025] In order to solve the technical problem of the present application, the technical solution of a method for preparing a low-warpage reinforced POM composite material of the present application will be specifically described below.

[0026] A method for preparing a low-warping reinforced POM composite material comprises a carbon fiber modification treatment part and a component mixing and granulation part.

[0027] in:

[0028] The carbon fiber modification process includes carbon fiber cleaning, surface oxidation and chemical grafting.

[0029] The carbon fiber modification processing part is used to provide modified carbon fiber to the component mixing and granulation part, so as to reduce the amount of carbon fiber used and achieve low warping, and solve the problem that the existing technology needs to add a large amount of carbon fiber to produce polymer composite materials, which makes it difficult to use them widely and on a large scale.

[0030] It should be noted that the cleaning of carbon fiber is to rinse with deionized water at 40-60°C for 20-40s. Generally, gentle rinsing is used to control the water flow speed and direction, reduce the vertical rinsing time, and rinse at an angle of 30° to 60° is the best, so as to avoid damage to the surface of carbon fiber caused by the impact of water flow. At the same time, the surface oxidation of carbon fiber is carried out by anodic electrolytic oxidation, and the cleaned carbon fiber is used as the anode, the electrolyte is sodium hydroxide, nitric acid, hydrochloric acid or potassium permanganate, and the voltage is controlled to be 1.4-1.8V. Finally, deionized water is used to rinse the surface oxidized carbon fiber to avoid acid-base imbalance caused by electrolyte adhesion and affect the subsequent processing effect of carbon fiber. According to the test, the carbon fiber treated with surface oxidation has the effect of improving chemical grafting when the oxygen content is 0.1%-12%. At the same time, chemical grafting is to immerse the surface oxidized carbon fiber in a 0.1-0.8% organic silane solution, and then take it out and treat it with cold plasma; wherein, the solvent is acetone, and the chemical formula of organic silane is as follows:

[0031] R2CH2NH(CH2)3Si(OR1)3

[0032] In the formula: R1 is C1-C4 alkyl; R2 is -CN, -NH2, -Cl, -Br or -HSO3.

[0033] The component mixing and granulation part includes the following steps:

[0034] Step 1, mixing: 80-100 parts by weight of POM, 12-18 parts of polycrystalline mullite fiber, 7-10 parts of glass fiber, 0.2-0.6 parts of anti-aging additive, and 0-3 parts of functional additive are put into a mixer and mixed evenly to obtain a mixture;

[0035] Step 2, crushing: introducing the mixture into a crushing and grinding machine for crushing and grinding to obtain a powder mixture;

[0036] Step 3, drying: vacuum drying the powder mixture to obtain a dry mixture;

[0037] Step 4, granulation: the dry mixed material and 2-5 parts by weight of modified carbon fiber are introduced into a twin-screw extruder respectively, and melt-extruded to granulate.

[0038] In step 1, the anti-aging agent selected is a hindered phenol antioxidant. The functional additive includes a formaldehyde adsorbent and / or a lubricant. The formaldehyde adsorbent used in the embodiment of the present application is copolyamide COPA, and the lubricant is a silicone masterbatch, PE wax or calcium stearate. In step 2, the particle size of the powder mixture is less than 200nm.

[0039] It should be mentioned that the carbon fiber used in the embodiments of the present application is nano carbon fiber purchased from Beijing Mairida Technology Co., Ltd.

[0040] Embodiment 1

[0041] A method for preparing a low-warping reinforced POM composite material comprises a carbon fiber modification treatment part and a component mixing and granulation part.

[0042] in:

[0043] The carbon fiber modification process includes carbon fiber cleaning, surface oxidation and chemical grafting.

[0044] The carbon fiber modification processing part is used to provide modified carbon fiber to the component mixing and granulation part, so as to reduce the amount of carbon fiber used and achieve low warping, and solve the problem that the existing technology needs to add a large amount of carbon fiber to produce polymer composite materials, which makes it difficult to use them widely and on a large scale.

[0045] It should be noted that the cleaning of the carbon fiber is carried out by rinsing with deionized water at 40°C for 40s. At the same time, the surface oxidation of the carbon fiber is carried out by anodic electrolytic oxidation, and the cleaned carbon fiber is used as the anode, the electrolyte is sodium hydroxide, and the voltage is controlled to be 1.4V. Finally, the surface oxidized carbon fiber is rinsed with deionized water to avoid acid-base imbalance caused by electrolyte adhesion and affect the subsequent processing effect of the carbon fiber. According to the test, the oxygen content of the carbon fiber after surface oxidation treatment is 1.6%. At the same time, chemical grafting is carried out by immersing the surface oxidized carbon fiber in a 0.1% organic silane solution, and then taking it out and treating it with cold plasma. Among them, the solvent is acetone, and the chemical formula of organic silane is as follows:

[0046] R2CH2NH(CH2)3Si(OR1)3

[0047] In the formula: R1 is methane; R2 is -CN.

[0048] The component mixing and granulation part includes the following steps:

[0049] Step 1, mixing: 80 parts by weight of POM, 12 parts of polycrystalline mullite fiber, 7 parts of glass fiber, and 0.2 parts of anti-aging additive are put into a mixer and mixed evenly to obtain a mixture;

[0050] Step 2, crushing: introducing the mixture into a crushing and grinding machine for crushing and grinding to obtain a powder mixture with a particle size of less than 200 nm;

[0051] Step 3, drying: vacuum drying the powder mixture to obtain a dry mixture;

[0052] Step 4, granulation: the dry mixture and 2 parts by weight of modified carbon fiber are introduced into a twin-screw extruder respectively, and melt-extruded to granulate.

[0053] Embodiment 2

[0054] A method for preparing a low-warping reinforced POM composite material comprises a carbon fiber modification treatment part and a component mixing and granulation part.

[0055] in:

[0056] The carbon fiber modification process includes carbon fiber cleaning, surface oxidation and chemical grafting.

[0057] The carbon fiber modification processing part is used to provide modified carbon fiber to the component mixing and granulation part, so as to reduce the amount of carbon fiber used and achieve low warping, and solve the problem that the existing technology needs to add a large amount of carbon fiber to produce polymer composite materials, which makes it difficult to use them widely and on a large scale.

[0058] It should be noted that the cleaning of the carbon fiber is carried out by rinsing with deionized water at 50°C for 30 seconds. At the same time, the surface oxidation of the carbon fiber is carried out by anodic electrolytic oxidation, and the cleaned carbon fiber is used as the anode, the electrolyte is 40% nitric acid, and the voltage is controlled to be 1.8V. Finally, the surface oxidized carbon fiber is rinsed with deionized water to avoid acid-base imbalance caused by electrolyte adhesion and affect the subsequent processing effect of the carbon fiber. According to the test, the oxygen content of the carbon fiber treated with surface oxidation is 5.2%. At the same time, chemical grafting is carried out by immersing the surface oxidized carbon fiber in a 0.4% organic silane solution, and then taking it out and treating it with cold plasma. Among them, the solvent is acetone, and the chemical formula of organic silane is as follows:

[0059] R2CH2NH(CH2)3Si(OR1)3

[0060] In the formula: R1 is ethyl; R2 is -HSO3.

[0061] The component mixing and granulation part includes the following steps:

[0062] Step 1, mixing: 90 parts by weight of POM, 15 parts of polycrystalline mullite fiber, 8 parts of glass fiber, and 0.4 parts of anti-aging additive are put into a mixer and mixed evenly to obtain a mixture;

[0063] Step 2, crushing: introducing the mixture into a crushing and grinding machine for crushing and grinding to obtain a powder mixture with a particle size of less than 200 nm;

[0064] Step 3, drying: vacuum drying the powder mixture to obtain a dry mixture;

[0065] Step 4, granulation: the dry mixture and 3 parts by weight of modified carbon fiber are introduced into a twin-screw extruder respectively, and melt-extruded to granulate.

[0066] Embodiment 3

[0067] A method for preparing a low-warping reinforced POM composite material comprises a carbon fiber modification treatment part and a component mixing and granulation part.

[0068] in:

[0069] The carbon fiber modification process includes carbon fiber cleaning, surface oxidation and chemical grafting.

[0070] The carbon fiber modification processing part is used to provide modified carbon fiber to the component mixing and granulation part, so as to reduce the amount of carbon fiber used and achieve low warping, and solve the problem that the existing technology needs to add a large amount of carbon fiber to produce polymer composite materials, which makes it difficult to use them widely and on a large scale.

[0071] It should be noted that the cleaning of the carbon fiber is carried out by rinsing with deionized water at 60°C for 20s. At the same time, the surface oxidation of the carbon fiber is carried out by anodic electrolytic oxidation, and the cleaned carbon fiber is used as the anode, the electrolyte is hydrochloric acid, and the voltage is controlled to be 1.5V. Finally, the surface oxidized carbon fiber is rinsed with deionized water to avoid acid-base imbalance caused by electrolyte adhesion and affect the subsequent processing effect of the carbon fiber. According to the test, the oxygen content of the carbon fiber after surface oxidation treatment is 10.6%. At the same time, chemical grafting is carried out by immersing the surface oxidized carbon fiber in a 0.8% organic silane solution, and then taking it out and treating it with cold plasma. Among them, the solvent is acetone, and the chemical formula of organic silane is as follows:

[0072] R2CH2NH(CH2)3Si(OR1)3

[0073] In the formula: R1 is ethyl; R2 is -Br.

[0074] The component mixing and granulation part includes the following steps:

[0075] Step 1, mixing: 100 parts by weight of POM, 18 parts of polycrystalline mullite fiber, 10 parts of glass fiber, and 0.6 parts of anti-aging additive are put into a mixer and mixed evenly to obtain a mixture;

[0076] Step 2, crushing: introducing the mixture into a crushing and grinding machine for crushing and grinding to obtain a powder mixture with a particle size of less than 200 nm;

[0077] Step 3, drying: vacuum drying the powder mixture to obtain a dry mixture;

[0078] Step 4, granulation: the dry mixed material and 5 parts by weight of modified carbon fiber are introduced into a twin-screw extruder respectively, and melt-extruded and granulated.

[0079] Embodiment 4

[0080] A method for preparing a low-warping reinforced POM composite material comprises a carbon fiber modification treatment part and a component mixing and granulation part.

[0081] in:

[0082] The carbon fiber modification process includes carbon fiber cleaning, surface oxidation and chemical grafting.

[0083] The carbon fiber modification processing part is used to provide modified carbon fiber to the component mixing and granulation part, so as to reduce the amount of carbon fiber used and achieve low warping, and solve the problem that the existing technology needs to add a large amount of carbon fiber to produce polymer composite materials, which makes it difficult to use them widely and on a large scale.

[0084] It should be noted that the cleaning of the carbon fiber is carried out by rinsing with deionized water at 40°C for 40s. At the same time, the surface oxidation of the carbon fiber is carried out by anodic electrolytic oxidation, and the cleaned carbon fiber is used as the anode, the electrolyte is sodium hydroxide, and the voltage is controlled to be 1.4V. Finally, the surface oxidized carbon fiber is rinsed with deionized water to avoid acid-base imbalance caused by electrolyte adhesion and affect the subsequent processing effect of the carbon fiber. According to the test, the oxygen content of the carbon fiber after surface oxidation treatment is 1.6%. At the same time, chemical grafting is carried out by immersing the surface oxidized carbon fiber in a 0.1% organic silane solution, and then taking it out and treating it with cold plasma. Among them, the solvent is acetone, and the chemical formula of organic silane is as follows:

[0085] R2CH2NH(CH2)3Si(OR1)3

[0086] In the formula: R1 is methane; R2 is -CN.

[0087] The component mixing and granulation part includes the following steps:

[0088] Step 1, mixing: 80 parts by weight of POM, 12 parts of polycrystalline mullite fiber, 7 parts of glass fiber, 0.2 parts of anti-aging additive, and 1 part of functional additive are put into a mixer and mixed evenly to obtain a mixture;

[0089] Step 2, crushing: introducing the mixture into a crushing and grinding machine for crushing and grinding to obtain a powder mixture with a particle size of less than 200 nm;

[0090] Step 3, drying: vacuum drying the powder mixture to obtain a dry mixture;

[0091] Step 4, granulation: the dry mixture and 2 parts by weight of modified carbon fiber are introduced into a twin-screw extruder respectively, and melt-extruded to granulate.

[0092] Functional additives include formaldehyde adsorbents and lubricants. In the embodiment of the present application, the formaldehyde adsorbent used is copolyamide COPA, and the lubricant is silicone masterbatch.

[0093] Embodiment 5

[0094] A method for preparing a low-warping reinforced POM composite material comprises a carbon fiber modification treatment part and a component mixing and granulation part.

[0095] in:

[0096] The carbon fiber modification process includes carbon fiber cleaning, surface oxidation and chemical grafting.

[0097] The carbon fiber modification processing part is used to provide modified carbon fiber to the component mixing and granulation part, so as to reduce the amount of carbon fiber used and achieve low warping, and solve the problem that the existing technology needs to add a large amount of carbon fiber to produce polymer composite materials, which makes it difficult to use them widely and on a large scale.

[0098] It should be noted that the cleaning of the carbon fiber is carried out by rinsing with deionized water at 40°C for 40s. At the same time, the surface oxidation of the carbon fiber is carried out by anodic electrolytic oxidation, and the cleaned carbon fiber is used as the anode, the electrolyte is sodium hydroxide, and the voltage is controlled to be 1.4V. Finally, the surface oxidized carbon fiber is rinsed with deionized water to avoid acid-base imbalance caused by electrolyte adhesion and affect the subsequent processing effect of the carbon fiber. According to the test, the oxygen content of the carbon fiber after surface oxidation treatment is 1.6%. At the same time, chemical grafting is carried out by immersing the surface oxidized carbon fiber in a 0.1% organic silane solution, and then taking it out and treating it with cold plasma. Among them, the solvent is acetone, and the chemical formula of organic silane is as follows:

[0099] R2CH2NH(CH2)3Si(OR1)3

[0100] In the formula: R1 is ethyl; R2 is -NH2.

[0101] The component mixing and granulation part includes the following steps:

[0102] Step 1, mixing: 80 parts by weight of POM, 12 parts of polycrystalline mullite fiber, 7 parts of glass fiber, 0.2 parts of anti-aging additive, and 1 part of functional additive are put into a mixer and mixed evenly to obtain a mixture;

[0103] Step 2, crushing: introducing the mixture into a crushing and grinding machine for crushing and grinding to obtain a powder mixture with a particle size of less than 200 nm;

[0104] Step 3, drying: vacuum drying the powder mixture to obtain a dry mixture;

[0105] Step 4, granulation: the dry mixture and 2 parts by weight of modified carbon fiber are introduced into a twin-screw extruder respectively, and melt-extruded to granulate.

[0106] The functional auxiliary agent includes a lubricant, and the lubricant is calcium stearate.

[0107] Comparative Example 1

[0108] The difference between Comparative Example 1 and Example 1 is that the carbon fiber used in Comparative Example 1 has not been subjected to chemical grafting treatment.

[0109] Comparative Example 2

[0110] The difference between Comparative Example 2 and Example 1 is that the concentration of the organosilane used in Comparative Example 2 is 1.0%.

[0111] Comparative Example 3

[0112] The difference between Comparative Example 3 and Example 1 is that the organosilane used in Comparative Example 3 is vinyl (β-methoxyethoxy) silane coupling agent A172.

[0113] Comparative Example 4

[0114] The difference between Comparative Example 4 and Example 1 is that no polycrystalline mullite fiber is added in step 1 of Comparative Example 4.

[0115] Comparative Example 5

[0116] The difference between Comparative Example 5 and Comparative Example 4 is that the carbon fiber used in Comparative Example 5 has not been subjected to chemical grafting treatment.

[0117] Performance tests were performed on Examples 1 to 5 and Comparative Examples 1 to 5, and the test contents and methods are as follows:

[0118] 1. Tensile properties: According to ISO527-2 specimen size, injection molding standard specimen test, control the test rate to 5mm / min, the test temperature is room temperature 23℃;

[0119] 2. Bending performance: According to the IS178 spline size, injection molding standard spline test, the test span is 64mm, the test rate is 2mm / min, and the test temperature is room temperature 23℃;

[0120] 3. Vicat softening temperature test: According to ISO 306 standard, the specimen specification is 10*10*3.2mm, the test condition is B50, the applied load is 50N, and the heating rate is 50℃ / h;

[0121] 4. Warpage test: The granulated material is injection molded into 100*100 flat plates with thicknesses of 2.0 and 3.2 mm respectively. They are placed in a constant temperature and humidity environment for 48 hours and then the maximum warpage height is tested.

[0122] The performance test results are shown in Table 1 below:

[0123] Table 1 Performance test results

[0124]

[0125] It can be known from the above table that the preparation method of the low-warping enhanced POM composite material of the present application is mixed by adopting the combined components of modified carbon fiber and polycrystalline mullite fiber, so that polycrystalline mullite fiber and modified carbon fiber cooperate with each other to achieve the effects of low warping, high temperature resistance and high strength, and the manufacturing cost will be significantly reduced due to the decrease in the content of carbon fiber. Among them, it can be seen from Example 1, Comparative Example 4 and Comparative Example 5 that polycrystalline mullite fiber can play a role in improving the Vicat softening temperature, but will have a negative impact on tensile strength and flexural strength, thereby affecting the low warping ability of the low-warping enhanced POM composite material prepared by the preparation method of the low-warping enhanced POM composite material. At the same time, it can be found from Example 1 to Example 3 that by increasing the content of modified carbon fiber, there will be an effect of improving tensile strength and flexural strength, thereby achieving the effect of low warping track. By combining Example 1 with Comparative Example 2 and Example 1 with Comparative Example 3, it can be found that by adopting the organic silane of the concentration of the present application, the contribution of the modified carbon fiber to the mechanical properties of the low-warping reinforced POM composite material after chemical grafting treatment will be significantly improved. This is because the interfacial bonding force is significantly improved with the grafting reaction of the organic silane of the present application with the carbon fiber treated with surface oxidation, and thus the ILSS measured in Example 1 is 56.4 MPa, compared with the ILSS measured for the composite material of Comparative Example 1 of 154.1 MPa, resulting in an ILSS increase of 173%.

[0126] In summary, the present application provides a method for preparing a low-warping reinforced POM composite material. The method for preparing a low-warping reinforced POM composite material adopts modified carbon fibers that have been cleaned, surface oxidized and chemically grafted, so that the surface monomer adsorption capacity of the carbon fibers after surface oxidation is improved, and then after the organic silane is used as a monomer and chemically grafted with the carbon fibers, when mixed with POM, polycrystalline mullite fiber and glass fiber as main components for melt extrusion and granulation, the fiber pull-out phenomenon using the fracture is significantly reduced, and the method has the effects of high shear strength, excellent interface bonding strength and significantly improved interlaminar shear strength ILSS.

[0127] The "first", "second", "third", "fourth", etc. (if any) referred to in this application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments described herein can be implemented in an order other than that described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method or device comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods or devices.

[0128] It should be noted that the descriptions involving "first", "second", etc. in this application are only for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by this application.

[0129] Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A method for preparing a low-warpage reinforced POM composite material, characterized in that: It includes a carbon fiber modification processing part and a component mixing and granulation part; The carbon fiber modification treatment part includes cleaning, surface oxidation and chemical grafting of carbon fibers; the component mixing and granulation part includes the following steps: Step 1, mixing: 80-100 parts by weight of POM, 12-18 parts of polycrystalline mullite fiber, 7-10 parts of glass fiber, and 0.2-0.6 parts of anti-aging additive are put into a mixer and mixed evenly to obtain a mixture; Step 2, crushing: introducing the mixture into a crushing and grinding machine for crushing and grinding to obtain a powder mixture; Step 3, drying: vacuum drying the powder mixture to obtain a dry mixture; Step 4, granulation: introducing the dry mixed material and 2-5 parts by weight of the modified carbon fiber into a twin-screw extruder respectively, and melt-extruding and granulating; Wherein, the chemical grafting is an organosilane grafting treatment using the following molecular formula: R2CH2NH(CH2)3Si(OR1)3 In the formula: R1 is C1-C4 alkyl; R2 is -CN, -NH2, -Cl, -Br or -HSO3.

2. The method for preparing a low-warpage reinforced POM composite material according to claim 1, characterized in that: The carbon fiber is cleaned by rinsing with deionized water at 40-60°C for 20-40s, and the surface oxidation of the carbon fiber is carried out by anodic electrolytic oxidation, with the cleaned carbon fiber used as the anode, the electrolyte being sodium hydroxide, nitric acid, hydrochloric acid or potassium permanganate, and the voltage being controlled at 1.4-1.8V, and the surface oxidized carbon fiber is rinsed with deionized water.

3. The method for preparing a low-warpage reinforced POM composite material according to claim 1, characterized in that: The oxygen content of the surface-oxidized carbon fiber is 0.1%-12%.

4. The method for preparing a low-warpage reinforced POM composite material according to claim 1, characterized in that: The chemical grafting is carried out by immersing the surface-oxidized carbon fibers in an organic silane solution with a concentration of 0.1-0.8%, and then taking them out and subjecting them to cold plasma treatment; wherein the solvent is acetone.

5. The method for preparing a low-warpage reinforced POM composite material according to claim 1, characterized in that: The anti-aging aid is a hindered phenol antioxidant.

6. The method for preparing a low-warpage reinforced POM composite material according to claim 1, characterized in that: The particle size of the powder mixture is less than 200 nm.

7. The method for preparing a low-warpage reinforced POM composite material according to claim 1, characterized in that: The mixture further comprises 0-3 parts by weight of a functional aid, wherein the functional aid comprises a formaldehyde adsorbent and / or a lubricant.

8. The method for preparing a low-warpage reinforced POM composite material according to claim 7, characterized in that: The formaldehyde adsorbent is copolyamide COPA, and the lubricant is silicone masterbatch, PE wax or calcium stearate.

Citation Information

Patent Citations

  • Mineral reinforced low-warpage POM material and preparation process thereof

    CN109825028A